2014
DOI: 10.1051/swsc/2014013
|View full text |Cite
|
Sign up to set email alerts
|

Ionosphere Waves Service (IWS) – a problem-oriented tool in ionosphere and Space Weather research produced by POPDAT project

Abstract: In the frame of the FP7 POPDAT project the Ionosphere Waves Service (IWS) has been developed and opened for public access by ionosphere experts. IWS is forming a database, derived from archived ionospheric wave records to assist the ionosphere and Space Weather research, and to answer the following questions: How can the data of earlier ionospheric missions be reprocessed with current algorithms to gain more profitable results? How could the scientific community be provided with a new insight on wave processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A general review of the various methods employed for ELF/VLF signal detection can be found in Ferencz et al. (2014). Algorithms such as those utilized by AWDA are extremely useful; however, such methods can be difficult to rely on in new noisy environments (as seen in ground‐based data) and do not easily generalize to new signal classes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general review of the various methods employed for ELF/VLF signal detection can be found in Ferencz et al. (2014). Algorithms such as those utilized by AWDA are extremely useful; however, such methods can be difficult to rely on in new noisy environments (as seen in ground‐based data) and do not easily generalize to new signal classes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the AWDA (Automated Whistler Detector and Analyzer) system, uses a canonical frequency-time spectrum of a mid-latitude whistler based on a dispersion relation to detect whistlers only after a lengthy noise-removal and amplitude thresholding process (Lichtenberger et al, 2008). A general review of the various methods employed for ELF/VLF signal detection can be found in Ferencz et al (2014). Algorithms such as those utilized by AWDA are extremely useful; however, such methods can be difficult to rely on in new noisy environments (as seen in ground-based data) and do not easily generalize to new signal classes.…”
mentioning
confidence: 99%
“…Automation is possible by the machine learning that required a specific representation and characterization. In the past many scientists were working on automatic detection of VLF emission (Buzzi,2006;Linchtenbeger et al, 2008;Ferencz et al, 2009;Golden et al, 2011;Ferencz et al, 2014) by analysis of the spectrogram of VLF signals. As we know that the VLF signals are non-stationary signals and spectrogram is constructed by using Short Time Fourier transform (STFT) in which signal segment within the window function is assumed to be stationary (Akay,1997).…”
Section: Introductionmentioning
confidence: 99%